Uji Mikrobiologi Kualitas Air Minum Damiu di Kelurahan Karanganyar Gunung Kota Semarang - Thoriq Alghony; Ana Yustika; Ana Khoirul Ummah; Aprin Wahyu Wijayanti; Prasojo Prasojo (STIKES HAKLI Semarang, 2025)
Drinking water is a basic need that is very important for human health. One of the alternative drinking water supply that is widely used by the community is the Refillable Drinking Water Depot (DAMIU). This study aims to determine the microbiological quality of DAMIU drinking water in Karanganyar Gunung Village, Semarang City. This type of research is an experiment with a total sampling method, where all DAMIU in the region (as many as 4 units) are used as research samples. The research procedure includes three stages of laboratory examination, namely preliminary test, affirmation test, and complementary test. The results of the study showed that of the 4 DAMIU examined, three of the DAMIUs (A, B, and C) met the standards because they did not contain Escherichia coli bacteria, so the drinking water was suitable and safe for public consumption. However, one DAMIU (D) was found to contain Escherichia coli, so the water quality was microbiologically unsuitable for health requirements. Some of the factors that are suspected to be the cause of the unworthiness are the lack of maintenance of production facilities and equipment, unhygienic processing processes, and personal hygiene of managers who are not in accordance with operational standards. These findings affirm the importance of periodic monitoring of DAMIU and increasing the capacity of managers in maintaining the hygiene and sanitation of the refillable drinking water production process. Thus, the community can still get safe, healthy, and suitable drinking water according to environmental health standards.